The melanin-concentrating hormone receptor 1, a novel target of autoantibody responses in vitiligo - E. Helen Kemp; Elizabeth A. Waterman; Brian E. Hawes; Kim O’Neill; Raju V.S.R.K. Gottumukkala; David J. Gawkrodger; Anthony P. Weetman; Philip F. Watson (The Journal of Clinical Investigation, 2002)
Vitiligo is a common depigmenting disorder resulting from the loss of melanocytes in the skin. The pathogenesis of the disease remains obscure, although autoimmune mechanisms are thought to be involved. Indeed, autoantibodies and autoreactive T lymphocytes that target melanocytes have been reported in some vitiligo patients. The objective of this study was to identify pigment cell antigens that are recognized by autoantibodies in vitiligo. Using IgG from vitiligo patients to screen a melanocyte cDNA phage-display library, we identified the melanin-concentrating hormone receptor 1 (MCHR1) as a novel autoantigen related to this disorder. Immunoreactivity against the receptor was demonstrated in vitiligo patient sera by using radiobinding assays. Among sera from healthy controls and from patients with autoimmune disease, none exhibited immunoreactivity to MCHR1, indicating a high disease specificity for Ab’s against the receptor. Inhibition of MCH binding to its receptor by IgG from vitiligo patients was also shown.